Challenges of Assessing Community Mortality Due to Respiratory Viruses in Children Aged Less Than 5 Years - Caballero, Mauricio T; Satav, Ashish; Gill, Christopher J; Omer, Saad B; Pieciak, Rachel C; Kazi, Abdul Momin; Simões, Eric Af; Polack, Fernando P (Clinical infectious diseases, 2021)
Abstract Background Estimating the real impact of respiratory syncytial virus (RSV) disease is key for the development of vaccines and treatments. Ascertaining the burden of community mortality due to RSV is challenging due to the lack of primary data. Therefore, conducting observational studies to determine the factors associated with community mortality due to the virus in developing countries is important. Objective Our aim in this study was to describe the obstacles, gaps, and challenges that investigators face in low-income, vulnerable regions in 4 developing countries on 3 continents. Results The main obstacles and challenges of ascertaining community mortality due to RSV were defining strategies to consent families for testing before burial, sampling individuals at the household level, supporting bereaved parents with different cultural and religious backgrounds, establishing tailored strategies for studies in challenging settings, and integrating RSV mortality data from nasopharyngeal samples. Conclusion Detailed logistical planning based on population sociodemographic information, grief counseling, staff training, and a multidisciplinary approach with adequate laboratory infrastructure is critical to successful observational community-based RSV studies.